Emulsion-Type Chicken Sausage Quality with Fat Substitution by Rice Starches during Freeze-Thaw Cycles - Kosim, A.; Rumpagaporn, P.; Vangnai, K. (Faculty of Animal Science, IPB University, 2025)
The potential of rice starch types was explored to mimic the fat and improve the stability of chicken sausage during multiple freeze-thaw (F-T) cycles. This study investigated the effect of partial fat replacement with non-waxy and waxy rice starch on the physical properties of chicken sausage during multiple F-T cycles. Sausages were manufactured using eight different formulas (standard fat, reduced-fat, and reduced-fat with both starches at addition levels of 3%, 6%, and 9%). Emulsion stability, cooking loss, color, and texture profile were analyzed as initial qualities. Sausages were stored at -18 oC for seven days and thawed at 4 oC for 17 h for each of three F-T cycles, then thawing loss and texture were evaluated. The result showed that the incorporation of non-waxy and waxy rice starch up to 9% increased the emulsion stability, lightness (L*), and the value of hardness, gumminess, and chewiness of chicken sausage (p<0.05). Multiple F-T cycles lead to mechanical damage and quality deterioration, including water-holding capacity loss and textural change. The thawing loss value of all treatments significantly increased during the F-T cycle. Utilization of waxy rice starch 3% in low-fat chicken sausage exhibited optimum physical properties and minimum thawing loss and texture change during multiple F-T cycles.